2008
DOI: 10.1016/j.regpep.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Brain circuits regulating energy homeostasis

Abstract: Recent years have seen an impetus in the study for central mechanisms regulating energy balance, and caloric intake possibly as a response to the obesity pandemic. This renewed interest as well as drastic improvements in the tools that are now currently available to neuroscientists, has yielded a great deal of insight into the mechanisms by which the brain regulates metabolic function, and volitional aspects of feeding in response to metabolic signals like leptin, insulin and ghrelin. Among these mechanisms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 149 publications
0
135
0
Order By: Relevance
“…Hypothalamic nuclei have a well-established role in modulating energy homeostasis and feeding regulation; lesions of ventromedial, paraventricular, and dorsomedial nuclei or stimulation of the lateral hypothalamus (LH) produce hyperphagia, whereas lesions of the LH inhibit feeding (20). More specifically, the arcuate nucleus (Arc) lies close to the third ventricle; thus, circulating satiety and/or hunger signals, including those secreted from fat tissue, pancreas, and the gut, easily interact with this nucleus.…”
Section: Mechanistic Pathways Linking Central and Peripheral Control mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothalamic nuclei have a well-established role in modulating energy homeostasis and feeding regulation; lesions of ventromedial, paraventricular, and dorsomedial nuclei or stimulation of the lateral hypothalamus (LH) produce hyperphagia, whereas lesions of the LH inhibit feeding (20). More specifically, the arcuate nucleus (Arc) lies close to the third ventricle; thus, circulating satiety and/or hunger signals, including those secreted from fat tissue, pancreas, and the gut, easily interact with this nucleus.…”
Section: Mechanistic Pathways Linking Central and Peripheral Control mentioning
confidence: 99%
“…Arc neurons produce and respond to neuropeptide Y (NPY), agouti-related protein (AgRP), proopiomelanocortin (POMC), and cocaine-and amphetamine-regulated transcript (CART) to influence feeding behavior and energy homeostasis (21,22). In fact, discrete activation of these Arc neurons can facilitate alterations in behavior and energy expenditure; excitation of NPY/AgRP neurons increases food intake and decreases energy expenditure, and stimulation of POMC/CART receptors inhibits food intake and increases energy expenditure (20,23). Thus, some peripherally secreted substrates modulate feeding and energy expenditure via direct action on these cells within the Arc.…”
Section: Mechanistic Pathways Linking Central and Peripheral Control mentioning
confidence: 99%
“…26 It has been shown that neuronal damage is not only associated with structural and functional changes in the brain but also with disturbances in the immune system, energy homeostasis, autonomic stress response, and endocrine regulation. [27][28][29][30] Because it is not possible to make a causal inference based solely on our observation, this hypothesis needs to be tested in future studies investigating the long-term consequences of suboptimal CBF on major homeostatic mechanisms. Subgroup analysis on the association between cerebral blood flow and mortality…”
Section: Resultsmentioning
confidence: 99%
“…When fat stores are reduced and energy levels are low, hunger signals mediated via an increase in the gut hormone, ghrelin, and reductions in insulin, glucose, leptin and cholecystokinin (CCK) cause increases in the activity of both neuropeptide Y (NPY) and agouti-related protein (AgRP) neurons, which in turn leads to decreased activity of the melanocortin system, leading to disinhibition of melanin-concentrating hormone (MCH) and orexin (ORX) signalling producing a marked orexigenic effect. Following a meal the reverse occurs, with high levels of glucose, insulin, CCK and reduced ghrelin levels leading to increases in pro-opiomelanocortin (POMC) and cocaine-amphetamine regulated transcript (CART) neuronal activity, in turn increasing a-melanocyte-stimulating hormone (a-MSH) release and decreasing MCH/ORX activity, leading to satiation and a termination of feeding ( Figure 2) [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Hypothalamus and The Central Control Of Feeding And Energy Hmentioning
confidence: 99%
“…Pharmacological manipulation of these targets offers another approach to regulating food intake [11].…”
Section: Direct Modulation On Neuropeptide Transmitters Within the Hymentioning
confidence: 99%